The Role of Maternally Acquired Antibody in Providing Protective Immunity Against Nontyphoidal Salmonella in Urban Vietnamese Infants: A Birth Cohort Study. (12th October 2018) - de Alwis, Ruklanthi; Tu, Le Thi Phuong; Quynh, Nhi Le Thi; Thompson, Corinne N; Anders, Katherine L; Van Thuy, Nguyen Thi; Hieu, Nguyen Trong; Vi, Lu Lan; Chau, Nguyen Van Vinh; Duong, Vu Thuy; Chau, Tran Thi Hong; Tuyen, Ha Thanh; et al.
Abstract : We found a high transfer ratio of anti-nontyphoidal Salmonella (NTS) antibodies from mothers to infants. Furthermore, despite a high seroincidence of NTS in infants, maternally acquired antibodies provided protection from seroconversion. Therefore, we propose prenatal immunization against NTS as a possible strategy for protecting infants from NTS disease. Abstract: Background: Nontyphoidal Salmonella (NTS) organisms are a major cause of gastroenteritis and bacteremia, but little is known about maternally acquired immunity and natural exposure in infant populations residing in areas where NTS disease is highly endemic. Methods: We recruited 503 pregnant mothers and their infants (following delivery) from urban areas in Vietnam and followed infants until they were 1 year old. Exposure to the dominant NTS serovars, Salmonella enterica serovars Typhimurium and Enteritidis, were assessed using lipopolysaccharide (LPS) O antigen–specific antibodies. Antibody dynamics, the role of maternally acquired antibodies, and NTS seroincidence rates were modeled using multivariate linear risk factor models and generalized additive mixed-effect models. Results: Transplacental transfer of NTS LPS–specific maternal antibodies to infants was highly efficient. Waning of transplacentally acquired NTS LPS–specific antibodies at 4 months of age left infants susceptible to Salmonella organisms, after which they began to seroconvert. High seroincidences of S . Typhimurium and S . Enteritidis LPS were observed, and infants born with higher anti-LPS titers had greater plasma bactericidal activity and longer protection from seroconversion. Conclusions: Although Vietnamese infants have extensive exposure to NTS, maternally acquired antibodies appear to play a protective role against NTS infections during early infancy. These findings suggest that prenatal immunization may be an appropriate strategy to protect vulnerable infants from NTS disease.